The Mediating Role of Resilience in the Relationship Between Social Support and Self-Esteem among Fatherless Adolescents - Desliana Ayundhira Kamba, Revanita; Adinda Prabowo Putri, Siska; Zellawati, Alice (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Emotional pressures experienced by fatherless adolescents such as low self-confidence and loneliness highlight the importance of environmental support in helping them continue to develop positively. In this context, social support serves as a key factor that strengthens an individual's ability to cope and enhances their self-perception. This study aims to examine the influence of social support on self-esteem, with resilience as a mediating variable among fatherless adolescents in Semarang City. The subjects were adolescents aged 15–17 years who were experiencing fatherless conditions, selected using purposive sampling. This research employed a quantitative approach with a cross-sectional design, collecting data through psychological scales and analyzing it using path analysis. The results showed that social support has a positive and significant effect on both resilience and self-esteem (p < 0.05), and resilience was found to mediate the relationship between social support and self-esteem. Furthermore, the coefficient of determination indicated that social support and resilience together contribute approximately 31% to self-esteem. In other words, the higher the social support received, the stronger the resilience developed, which in turn leads to improved self-esteem among fatherless adolescents.Tekanan emosional seperti rasa tidak aman dan kesepian yang dialami oleh remaja tanpa kehadiran ayah menunjukkan betapa pentingnya peran lingkungan dalam mendorong perkembangan positif mereka. Dalam hal ini, dukungan sosial menjadi salah satu faktor penting yang dapat memperkuat resiliensi sekaligus membentuk penilaian diri yang lebih positif. Penelitian ini bertujuan untuk menguji pengaruh dukungan sosial terhadap harga diri dengan resiliensi sebagai variabel mediator pada remaja tanpa kehadiran ayah di Kota Semarang. Penelitian melibatkan remaja berusia 15–17 tahun yang dipilih menggunakan teknik purposive sampling. Dengan menggunakan pendekatan kuantitatif dan desain cross-sectional, data dikumpulkan melalui skala psikologis dan dianalisis menggunakan analisis jalur (path analysis). Hasil penelitian menunjukkan bahwa dukungan sosial berpengaruh positif dan signifikan terhadap resiliensi dan harga diri (p < 0,05), serta resiliensi terbukti memediasi hubungan antara keduanya. Nilai koefisien determinasi menunjukkan bahwa dukungan sosial dan resiliensi memberikan kontribusi terhadap harga diri sebesar ±31%. Dengan kata lain, semakin tinggi dukungan sosial yang diterima, semakin kuat resiliensi yang terbentuk, yang pada akhirnya berdampak pada peningkatan harga diri pada remaja tanpa kehadiran ayah.